Next‐generation polymerized human hemoglobins in hepatic bioreactor simulations. (21st January 2020) - Cuddington, Clayton; Moses, Savannah; Belcher, Donald; Ramesh, Niral; Palmer, Andre
Abstract: Hepatic hollow fiber (HF) bioreactors can be used to provide temporary support to patients experiencing liver failure. Before being connected to the patient's circulation, cells in the bioreactor must be exposed to a range of physiological O2 concentrations as observed in the liver sinusoid to ensure proper performance. This zonation in cellular oxygenation promotes differences in hepatocyte phenotype and may better approximate the performance of a real liver within the bioreactor. Polymerized human hemoglobin (PolyhHb) locked in the tense quaternary state (T‐state) has the potential to both supply and regulate O2 transport to cultured hepatocytes in the bioreactor due to its low O2 affinity. In this study, T‐state PolyhHb production and purification processes were optimized to minimize the concentration of low‐molecular‐weight PolyhHb species in solution. Deconvolution of size‐exclusion chromatography spectra was performed to calculate the distribution of polymeric Hb species in the final product. Fluid flow and mass transport within a single fiber of a hepatic HF bioreactor was computationally modeled with finite element methods to simulate the effects of employing T‐state PolyhHb to facilitate O2 transport in a hepatic bioreactor system. Optimal bioreactor performance was defined as having a combined hypoxic and hyperoxic volume fraction in the extracapillary space of less than 0.05 where multiple zones were observed. The Damköhler number and Sherwood number had strong inverse relationships at each cell density and fiber thickness combination. These results suggest that targeting a specific Damköhler number may be beneficial for optimal hepatic HF bioreactor operation.